Enhancing transdermal drug delivery: formulation and evaluation of simvastatin-loaded invasomes in carbopol gel for improved permeability and prolonged release - Deepak Kumar Dash; Dibya Sundar Panda; Satyanarayan Pattnaik; Riya Vaiswade; Gayatri Gupta (Brazilian Journal of Pharmaceutical Sciences)
Abstract The transdermal pathway serves as a significant route for achieving localized or systemic effects. Within this context, the stratum corneum is a crucial barrier limiting the permeation of many drugs. To surmount this barrier, carriers, and nanocarriers have been utilised, notably ‘invasome’ being one such example. In our study, we formulated invasomes loaded with simvastatin using the conventional thin-layer evaporation technique. This formulation involved the use of soy phosphatidylcholine, terpene (Limonene), chloroform, and ethanol. Simvastatin-loadedinvasomes were incorporated into a carbopol 934 solution to create a gel. We prepared and assessed different formulationsfor various parameters, including zeta potential, scanning electron microscopy, entrapment efficiency, viscosity, and drug content, and conducted in vitro studies. The entrapment efficiency was as high as 83.17±0.61%. The maximum in vitro drug permeation (45.44±0.4%) was found in the gel with 0.5% soy phosphatidylcholine and 0.25% terpene. Upon evaluating these parameters, our findings suggest that the simvastatin invasomal gel effectively enhances drug permeability across membranes and successfully achieves prolonged drug release.